Inflammatory and anti-inflammatoy response after swimming acute effort - Pussieldi, G. A.; Veneroso, C. E.; De Paz, J. A.; Teixeira, M. M. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2018)
The aimof the study was to analyze inflammatory and anti-inflammatory responses to an intense and acute swimming effort during the preparatory phase for the Brazilian National Adult Championship. Twenty swimmers participated. Plasma concentrations of IL-6, TNF-a, sTNFR1, IP-10 and MCP-1 were determined before and 40 minutes after 2 sets of 4 repetitions of 50 meters swam at maximum intensity with 3 minutes of recovery between each repetition and an active recovery swimming 1500m at low intensity after each of the two series. In response to acute exercise only the sTNFR1 concentration was reduced, with no changes in IP-10, IL-6 or TNF-a. Thus, acute exercise in swimming in well-trained people does not seem to produce an inflammatory response.